Association Between Myasthenia Gravis and Memory: A Systematic Review and Meta-Analysis - Zhou, Xiaoling; Zhou, Yifei; Hua, Jianian; Xue, Qun (Frontiers in Neurology, 2021)
Objective: Studies have produced contradictory results for the the association between myasthenia gravis (MG) and cognitive function, especially for the cognitive domains of memory. This meta-analysis dedicated to explore the association between myasthenia gravis and memory ability, which was represented by immediate recall and delayed recall. Methods: Adopting random-effects models, this study analyzed the memory ability in myasthenia gravis based on data from studies retrieved from four electronic databases from inception to February 2021. Results: There were totally eight studies of 274 patients and 211 healthy controls included. Significant associations were found between myasthenia gravis and memory ability. Compared with healthy control group, patients with myasthenia gravis performed significantly worse immediate recall (SMD= -0.65, 95% CI = -0.97~-0.33, p <0.001, I2 = 64.1%) and delayed recall (SMD= -0.49, 95% CI = -0.88~-0.1, p <0.05, I2 = 76.3%). Compared with patients with Class II MG, those with Class I MG did not have statistically different scores in immediate recall (SMD= -0.07, 95% CI = -0.35~0.21, p =0.614, I2 = 0%) and delayed recall (SMD= 0.63, 95% CI = -0.29~1.55, p =0.178, I2 = 87.9%). Conclusions: Patients with myasthenia gravis were impaired in memory ability,especially in immediate recall memory. There was no association between the severity of myasthenia gravis and memory ability. Future studies should address whether these associations are casual and modifiable.